THE IMPORTANCE OF LOGISTICS IN THE FOOD SECTOR AND A RESEARCH IN ÇORUM PROVINCE: LOGISTICS IN THE FOOD SECTOR - Cagiran Kendirli, Hulya; Turan, Altay Ural (Journal of Economic Development, Environment and People, 2024)
Food refers to all kinds of nutrients that people consume in order to survive and function in a healthy way. Food contains the nutrients necessary for the human body to meet its energy needs, grow, develop and maintain health. Foods are generally derived from natural sources and may undergo processing. It is important for people to have a balanced and varied diet to live a healthy life, as this helps provide all the nutrients the body needs. Logistics is a concept that refers to the management of processes responsible for the effective supply, storage, transportation, and distribution of goods and services. The purpose of these processes is to ensure that products or services are delivered to consumers or users at the right place, at the right time, and at the right cost. With this study, customer satisfaction in the logistics of businesses operating in the food sector in Çorum province, food safety, warehouse management, stock management, supply chain, data analytics in logistics, problems in transportation, important parts in food logistics, green logistics in the food sector, technological development in the food sector and food. A survey was conducted on the future of logistics in the sector. According to this research, it has been revealed that businesses have to follow the developments in food logistics and focus on customer satisfaction in order to hold on to the market in today's world. However, it has been revealed that since the products in the food industry are sensitive, that is, perishable, food safety should be given importance in logistics and the necessary precautions should be taken. It has been revealed that while businesses keep their products in the warehouse, they pay attention to the tracking system in the warehouse and stock management. According to the results obtained from the research, businesses expressed that they were open to current developments on the mentioned issues and stated that they followed these issues carefully. They noted that they pay extreme attention to the problems and difficulties that may arise during transportation and in the supply chain in food logistics. They said that they attach importance to knowledge in transportation and shipping, and noted that they pay attention to data storage and backups along with technology. According to the results obtained from the study, businesses also stated that they engage in activities that do not harm the environment while carrying out their logistics activities.